Study of Sustainable Environmental Management in Plaju Ulu Subdistrict, Plaju District, Palembang City - Sulistyani, Sulistyani; Bakhtiar Fahmi Fuadi (Prospect Publishing, 2024)
The production activities of the home-based tempeh industry generate liquid and solid waste, which disrupts community activities, particularly in the urban slum area of Plaju Ulu Subdistrict, Plaju District, Palembang City. The dense residential areas, combined with the accumulation of household waste, result in an uncomfortable living environment, health issues, and social conflicts. Various sectors have collaborated to address the problems of slum settlements in Plaju Ulu Subdistrict, including the Tempeh Artisans Group, the Melati Women's Farmers Group, the Plaju Ulu Subdistrict government, and PT Kilang Pertamina International Refinery Unit III Plaju through environmental management initiatives, particularly in RW 01 and RW 02. This study aims to map the issues, potential impact, and outcomes of environmental management innovations in Plaju Ulu Subdistrict. Several innovations have emerged, including the management and utilization of waste for value-added products, the use of unproductive area for medicinal plants (TOGA), the adoption of innovative tools, and energy conversion supporting eco-friendly business processes. Positive impacts have resulted from the implementation of these innovations, including a reduction in BOD pollution by 12.1209 tons/year, a reduction in COD pollution by 51.215 tons/year, a decrease in TSS pollution by 18.10 tons/year, and water savings for yard plant use through hydroponic methods amounting to 97.2 liters/year. The utilization of liquid tempeh waste through fermentation and the mixing of EM4, containing essential nutrients such as N 1.24%, P2O5 5.54%, KO 1.34% (NPK), and C-Organic 5.803%, is crucial for plant growth. This initiative has increased productive area of 0.012 hectares in RW 01 and RW 02, with a total of 1,500 plant units. Meanwhile, the hygienic drum innovation, which has been in place until 2024, has reduced emissions impacts by 30.804 kg CO2 eq for 20 tempeh production houses or home industries.